Relevance of diagnostic investigations in chronic inflammatory demyelinating poliradiculoneuropathy: Data from the Italian CIDP database. Issue 2 (13th May 2020) - Liberatore, Giuseppe; Manganelli, Fiore; Cocito, Dario; Fazio, Raffaella; Briani, Chiara; Filosto, Massimiliano; Benedetti, Luana; Antonini, Giovanni; Cosentino, Giuseppe; Jann, Stefano; Mazzeo, Anna; Cortese, Andrea; et al.
Abstract: The objective of our work was to report the clinical features and the relevance of diagnostic investigations in patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). We retrospectively reviewed data from patients with a clinical diagnosis of CIDP included in a national database. Among the 500 included patients with a clinical diagnosis of CIDP, 437 patients (87%) fulfilled the European Federation of Neurological Societies and Peripheral Nerve Society criteria for CIDP (definite in 407, probable in 26, possible in four). In 352 patients (86%) motor nerve conduction abnormalities consistent with demyelination were sufficient for the diagnosis of definite CIDP. In 55 patients, this diagnosis required the addition of one or two (from probable or from possible CIDP, respectively) supportive tests, while in 20 cases they improved the diagnosis from possible to probable CIDP, seven patients did not change diagnosis. Considering these 85 patients, cerebrospinal fluid studies were performed in 79 cases (93%) upgrading the certainty of diagnosis in 59% of examined patients. Sensory nerve conduction studies (NCS) were performed in 85% of patients with an improvement of diagnosis in 32% of cases. Nerve biopsy and ultrasound and magnetic resonance imaging (US/MRI) exams resulted positive in about 40% of examined patients, but they were performed in few patients (7 patients and 16 patients, respectively). A response to the therapy was present in 84% of treated patients (n = 77), contributing to support the diagnosis in 40 patients in whom the other supportive criteria were not sufficient. In most patients with CIDP the diagnosis is possible solely with motor NCS while other investigations may help improving the diagnosis in a minority of patients.